Using a Fully Expressive Avatar to Collaborate in Virtual Reality: Evaluation of Task Performance, Presence, and Attraction - Wu, Yuanjie; Wang, Yu; Jung, Sungchul; Hoermann, Simon; Lindeman, Robert W. (Frontiers in Virtual Reality, 2021)
Avatar mediated collaboration in virtual environments is becoming more and more prevalent. However, current consumer systems are not suited to fully replicate real-world non-verbal communication. We present a novel avatar system for collaboration in virtual reality, which supports high levels of non-verbal expression by tracking behavior such as body movement, hand gestures, and facial expressions. The system was built using camera tracking technology only. Therefore, in contrast to many other high-level tracking systems, it does not require users to wear additional trackers on their bodies. We compared our highly-expressive system with a consumer setup extended with two body-worn trackers in a dyadic study. We investigated users' performance, such as completion time and accuracy, as well as the presence and interpersonal attraction in a virtual charades game using an asymmetric control scheme. The results show that participants interacting with highly-expressive avatars felt more social presence and attraction and exhibit better task performance than those interacting with partners represented using low-expressive avatars. Hence, we conclude that virtual reality avatar systems benefit from a higher level of non-verbal expressiveness, which can be achieved without additional body-worn trackers.